DESCRIPTION OF ELECTROLYTE LEVELS IN PATIENTS DIABETES MELLITUS AT TOTO KABILA HOSPITAL KAB. BONE BOLANGO: DESCRIPTION OF ELECTROLYTE LEVELS IN PATIENTS DIABETES MELLITUS AT TOTO KABILA HOSPITAL KAB. BONE BOLANGO - Yusuf, Cindriyanti (Journal of Health, Technology and Science (JHTS), 2023)
This research aims to to know the description of electrolyte levels in patientswith diabetes mellitus at Toto Kabila Hospital, Bone Bolango Regency.The method in this study uses a descriptive qualitative approach. The type of dataused is data in the form of research results and secondary data in the form of datafrom literature, books, questionnaires, and medical records. The sampling techniquein this study used a purposive sampling technique, totaling 23 samples.Results This study shows that the percentage of electrolyte level examinationresults in patients with diabetes mellitus from 23 respondents obtained the results ofabnormal electrolyte levels examination 5 people (21.7%) and normal ones as manyas 18 people (78.3%).